The Relevance of Gold Investment from the Perspective of Sharia Economic Law (Study of DSN Fatwa Number: 77/DSN-MUI/V/2010) - Noor Asiah; Muhaimin; Zaki Mubarak (JOURNAL OF ISLAMIC AND LAW STUDIES, 2024)
This research was motivated by the determination of a fatwa on the ability to invest in gold as stated in the DSN fatwa Number: 77/DSN-MUI/V/2010 concerning Buying and Selling Gold Non-Cash. Therefore, the author analyzes what are the postulates underlying the determination of the DSN Fatwa NUMBER: 77/DSN-MUI/V/2010 and how relevant is the ability to invest in gold from the perspective of Sharia Economic Law. The method used according to its type is literature review and includes normative legal research. Meanwhile, the nature uses descriptive analysis research.The results of the study show that , first, the evidences underlying the determination of the Fatwa of DSN Number: 77/DSN-MUI/V/2010, namely Q.S al-Baqarah/2:275, the hadith of the narration of Ibn Majah and al-Baihaqi, Muslims, Abu Daud, Tirmizi, Nasa'i, the Rules of Ushul and the Rules of Fiqh, the fatwa of Ibn al-Qayyim, the fatwa of Imam Ibn Taymiyah, the fatwa of Shaykh 'Ali Jumu'ah, the fatwa of Shaykh Wahbah al-Zuhaily. So that these postulates become the basis for gold investment through the non-cash buying and selling of gold using murabahah contracts, buying and selling wakalah and rahn as long as gold is not an official medium of exchange (money), Second, gold investment based on Fatwa DSN NUMBER: 77/DSN-MUI/V/2010 concerning the non-cash buying and selling of gold if reviewed from the perspective of sharia economic law where the buying and selling transactions are non-cash and there is a delay in the receipt of goods to be traded is relevant according to the benefit of the ummah considering that gold is a good (sil'ah) that is sold and bought just like ordinary goods and is no longer tsaman (price, means of payment, money). Moreover, humans really need to buy and sell gold in installments. Gold has also been shaped into jewelry transformed into clothes and goods, and is not a tsaman (price, means of payment, money). So that there is no riba (in the exchange of buying and selling) between jewelry and the price (money), just as there is no riba (in the exchange of buying and selling) between the price (money) and other goods, even though it is not of the same type.